1994
DOI: 10.1111/j.2042-3306.1994.tb04054.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of exercise‐induced pulmonary haemorrhage in Quebec Standardbred racehorses

Abstract: Summary Sixty Standardbred horses, aged 3 to 10 years, were examined endoscopically for exercise‐induced pulmonary haemorrhage (EIPH) 1 h after racing, on at least 3 occasions. Racing time, finishing position and post exercise venous lactate concentrations were also recorded. Horses positive for tracheal blood on endoscopy were classified as having either grade 1 EIPH (one or a few spots of blood in the trachea), or grade 2 (stream of blood). Air temperature, relative humidity and air pollutant levels were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
74
2
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 8 publications
10
74
2
3
Order By: Relevance
“…Thereafter, separate trials were undertaken to determine the work intensity eliciting maximal heart rate and stress failure of pulmonary capillaries (25) leading to EIPH. In agreement with previous work, it was observed that galloping at 14 m/s on a 3.5% uphill grade not only elicited maximal heart rate but also induced EIPH in all horses, as demonstrated by the presence of fresh blood in the trachea on postexercise airway endoscopic examination (7,10,23), and could not be sustained for Ͼ120 s despite vigorous humane encouragement. Thus this workload was selected for further experimentation as representing maximal exertion for our horses.…”
Section: Exercise Training and Work Intensity Eliciting Maximal Heartsupporting
confidence: 92%
“…Thereafter, separate trials were undertaken to determine the work intensity eliciting maximal heart rate and stress failure of pulmonary capillaries (25) leading to EIPH. In agreement with previous work, it was observed that galloping at 14 m/s on a 3.5% uphill grade not only elicited maximal heart rate but also induced EIPH in all horses, as demonstrated by the presence of fresh blood in the trachea on postexercise airway endoscopic examination (7,10,23), and could not be sustained for Ͼ120 s despite vigorous humane encouragement. Thus this workload was selected for further experimentation as representing maximal exertion for our horses.…”
Section: Exercise Training and Work Intensity Eliciting Maximal Heartsupporting
confidence: 92%
“…Virtually all horses bred and trained for competitive racing show evidence of exercise-induced pulmonary hemorrhage (EIPH), which manifests as bleeding from the nose after exertion or the presence of red blood cells or hemosiderophages in the airways (3,6,21,39,47,53,58,67). The causative mechanism of EIPH was demonstrated experimentally when it was shown that high pulmonary capillary pressures can cause discrete breaks in the endothelium, epithelium, or the entire BGB in mammals (10,50,64,66).…”
mentioning
confidence: 99%
“…For this reason, some authors suggest performing endoscopic observations 30 to 90 min post exercise, extending to the tracheal carina. Horses positive for EIPH are classified in grades from I to IV, depending on the amount and anatomic location of the blood found (Lapointe et al 1994). Over the years, flexible endoscopy has been complemented by other diagnostic techniques such as X-rays, which allow for the identification of lobe pulmonary haemorrhage (Pascoe 1996(Pascoe , 1997.…”
Section: Diagnosis Of Exercise Induced Pulmonary Haemorrhagementioning
confidence: 99%
“…However, West et al (1993) observed episodes of EIPH in horses just after walking and trotting. There is a trend related to age, where older horses have shown increased susceptibility to episodes of EIPH (Lapointe et al 1994). Derksen (2009) suggested that increased prevalence of EIPH in older horses is due to progressive lung damage from repeated episodes of bleeding and the development of diseases of the upper airways.…”
mentioning
confidence: 99%